COLLECTION AND USE OF YOUR ENERGY DURING DRYING OF AGRICULTURAL PRODUCTS TECHNOLOGY - T. f.d. Prof. V. B. Qushimov Bakhtiyor Alishovich; The Big Arrow. Movlonov Pahlovon Ibroximovich,; Assistant. Bakirov Eldorbek Valijon ugli (Western European Studies, 2024)
In the article, it provides opportunities to increase efficiency through the use of thermal energy, drying and collecting. Vacuum-drying agent to the camera using the carrier provides methods of transmission of radiation'liq extra hot. Schemes energy and use it to collect and process developed.
Keywords: energy to gather; drying agricultural products; mode